2017
DOI: 10.3390/ijms18010140
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Proteins Control or Bypass p53 during Nucleolar Stress

Abstract: The nucleolus is the site of ribosome biogenesis, a complex process that requires the coordinate activity of all three RNA polymerases and hundreds of non-ribosomal factors that participate in the maturation of ribosomal RNA (rRNA) and assembly of small and large subunits. Nevertheless, emerging studies have highlighted the fundamental role of the nucleolus in sensing a variety of cellular stress stimuli that target ribosome biogenesis. This condition is known as nucleolar stress and triggers several response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
152
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(153 citation statements)
references
References 96 publications
1
152
0
Order By: Relevance
“…For example, NPM1 is able to interact directly with MDM2, independently of ARF, to inhibit p53/MDM2 and protect p53 from degradation (Kurki et al, 2004). Moreover, NPM1 has also been reported to directly associate with p53 for p53 stabilization and activation (Lambert and Buckle, 2006;Russo and Russo, 2017). We observed that NPM1 and p53 levels increased following the ribosomal stress caused by RGNNV infection.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…For example, NPM1 is able to interact directly with MDM2, independently of ARF, to inhibit p53/MDM2 and protect p53 from degradation (Kurki et al, 2004). Moreover, NPM1 has also been reported to directly associate with p53 for p53 stabilization and activation (Lambert and Buckle, 2006;Russo and Russo, 2017). We observed that NPM1 and p53 levels increased following the ribosomal stress caused by RGNNV infection.…”
Section: Discussionmentioning
confidence: 66%
“…The redistribution of nucleolar proteins plays an important role in nucleolar/ribosomal stress response (Russo and Russo, 2017). GS cells infected RGNNV were fixed at 24 h and the intracellular localization of RGNNV capsid protein and NPM1 were examined by indirect immunofluorescence (Fig.…”
Section: Rgnnv Induces Nucleolar/ribosomal Stress In Gs Cellsmentioning
confidence: 99%
“…Thus, only other nucleolar factors involved in the activation of appropriate pathways are taken into consideration. There is a growing body of evidence that RPs help to cope with unwelcome cells through their participation in pathways with or without p53 in response to the disruption of nucleolar function and integrity (Liu et al 2017b; Russo and Russo 2017). Recent studies point to the fact that RPs exhibit certain regularity of action during either fight with or generation of cancers.…”
Section: A Nucleolus As An Opponent Of Cancer Cells Via P53-dependentmentioning
confidence: 99%
“…Different proteins whose expression changes during stress as well as those nucleolar or ribosomal proteins which are released from nucleoli as a result of stress-induced nucleolar disintegration may contribute to the activation of pathways eliminating undesired cells. The mechanisms associated with activation of both pathways dependent on (Vlatkovic et al 2014) and independent of p53 (Chen et al 2016a; Russo and Russo 2017) participate in the nucleolar surveillance response. Since more than half of human cancers are devoid of functional p53 (Soussi 2000), it is especially important to find the p53-independent anticancer pathways.…”
Section: Nucleolus-mediated Anticancer Strategiesmentioning
confidence: 99%
“…Specifically, upon 5-FU induced nucleolar stress, a subset of rp including uL18 (rpL5), uL5 (rpL11), and uL14 (rpL23) are released from the ribosome to activate p53 through MDM2 inhibition [10]. Recently, our studies focused on post-transcriptional regulation [11,12,13,14] and extra-ribosomal functions of ribosomal proteins [11,15]. In particular, we demonstrated that uL3 (formerly rpL3) [16] is involved in the regulation of its own expression by regulating the splicing of its own transcript [17,18].…”
Section: Introductionmentioning
confidence: 99%